2015
DOI: 10.1016/j.phpro.2015.05.079
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ionizing Radiation on the Mechanical Properties of a Wood-Plastic Composite

Abstract: The focus of this study was to examine the potential benefits of irradiating polyethylene (PE)-based wood-plastic composites (WPCs) in order to enhance the mechanical properties of the WPC. The PE-based WPCs were irradiated, post extrusion, at dose levels of 0, 50, 100, 150, 200, and 250 kGy with an electron beam (EB). The irradiated WPCs were then evaluated using a third point bending test (ASTM D4761) along with scanning electron microscopy (SEM). It was found that ultimate strength and modulus of elasticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Ferreira et al (2014) have found that mechanical (tensile and impact) properties of High Density Polyethylene (HDPE)/ piassava fibre 70-30 w/w are improved after e-beam irradiation even at high irradiation dose (200 kGy), maybe because crosslinking is prominent in HDPE. Same observations were made by Palm et al (2015Palm et al ( , 2016 with increases of modulus, ultimate strength and hardness, after irradiation of PE-based wood plastic composites (WPCs) up to 250 kGy. The authors assumed that crosslinking of polyethylene dominated the degradation of cellulosic wood fibres inherent to irradiation, thus explaining the improved mechanical performances of irradiated WPCs.…”
Section: Direct Irradiation Of Natural Fibre Reinforced Compositesmentioning
confidence: 57%
“…Ferreira et al (2014) have found that mechanical (tensile and impact) properties of High Density Polyethylene (HDPE)/ piassava fibre 70-30 w/w are improved after e-beam irradiation even at high irradiation dose (200 kGy), maybe because crosslinking is prominent in HDPE. Same observations were made by Palm et al (2015Palm et al ( , 2016 with increases of modulus, ultimate strength and hardness, after irradiation of PE-based wood plastic composites (WPCs) up to 250 kGy. The authors assumed that crosslinking of polyethylene dominated the degradation of cellulosic wood fibres inherent to irradiation, thus explaining the improved mechanical performances of irradiated WPCs.…”
Section: Direct Irradiation Of Natural Fibre Reinforced Compositesmentioning
confidence: 57%
“…Exposure to the electron beam in polyethylene-based wood plastic composites boosted ultimate strength, modulus of elasticity (MOE), and moisture content (Palm et al, 2015). The tensile and in-planar characteristics of three-dimensional needled textile reinforcement on ceramic matrix composites (3DN CMCs) were investigated by Xu et al (Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…When cellulose, the primary structural component of wood, is exposed to electron beam radiation, the dominant reaction is cellulose chain scissoring . The resulting degradation of the wood particles may occur in a radiation crosslinked wood thermoplastic composite . On the other hand, lignin is the most radiation‐resistant component, because of its aromatic groups, protecting carbohydrates from radiation.…”
Section: Introductionmentioning
confidence: 99%